SST Based Medium Voltage Extreme Fast Charger for Electric Vehicles Using Fuzzy-PI and ANN Controllers - Arigela, Sai Lakshmi; Pandian, A. (International Journal of Integrated Engineering, 2024)
The development of power electronics devices and the integration of intelligent non-linear loads into the existing grid with the combination of various renewable sources along with batteries are increasing. For achieving the fast response in charging stations for electric vehicles, an efficient control strategies should be introduce when the renewable sources like PV is integrated with the grid along with battery. This paper proposes the utilization of Solid State Transformers replacing the conventional transformers for achieving the bidirectional power flow in addition to attain the better controlling over the system. To achieve the fast response in the charging station to the Electric vehicles traditional PI controller is replaced with the Fuzzy-PI and Artificial Neural Networks controllers and comparative analysis of these two are also done. The framework of the charging station is done by considering three different levels of voltages in view of achieving practical layout for the project. In order to demonstrate the proposed methods simulations are done using Matlab/Simulink